2019
DOI: 10.20944/preprints201903.0227.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Foliar Application of Y-Aminobutyric Acid (GABA) Improves Vegetative Growth, and the Physiological and Antioxidative Potential of Daucus Carota L. under Water Deficit Conditions

Abstract: Scarcity of water is one of the most serious concerns in plant biology with diverse implications at all the levels of molecular, biochemical, and physiological phenomena of plant growth, development, and consequently the productivity. Most of the strategies to induce or enhance drought tolerance in plants are unreasonably expensive and/or time-consuming. Some studies conducted in the recent past have shown that plant growth regulators (PGRs) may induce/improve physiological tolerance in plants to cope with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The GABA shunt has been associated with physiological responses, such as cytosolic pH regulation [86], nitrogen metabolism, and carbon fluxes into the Krebs cycle [87], protection against ROS production [88], and osmoregulation and signaling [89]. The GABA shunt is also involved in carbon and nitrogen metabolism, maintenance of cell membrane integrity [90], and minimizing the negative effects of abiotic stresses on plant metabolism [91].…”
Section: Gaba Shunt Activation In Response To Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The GABA shunt has been associated with physiological responses, such as cytosolic pH regulation [86], nitrogen metabolism, and carbon fluxes into the Krebs cycle [87], protection against ROS production [88], and osmoregulation and signaling [89]. The GABA shunt is also involved in carbon and nitrogen metabolism, maintenance of cell membrane integrity [90], and minimizing the negative effects of abiotic stresses on plant metabolism [91].…”
Section: Gaba Shunt Activation In Response To Drought Stressmentioning
confidence: 99%
“…Similarly, Tatar and Gevrek [135] reported an increase in the level of MDA in wheat as the duration of drought stress increased. Leaves of growing carrots (Daucus carota L.) accumulated high levels of MDA content under water deficit stress [91]. Morabito and Guerrier [136] reported that oxidative stress occurred 12 h after the application of drought stress.…”
Section: Oxidative Damage In Response To Drought Stressmentioning
confidence: 99%
“…Develop simplified LS-SVM and PLSR models. 5. Use the best model to predict the quality attributes of each sample pixel and compare its performance to Fig.…”
mentioning
confidence: 99%